Glucocorticoid Treatment in Community-Acquired Pneumonia - Dequin, Pierre-François; Confalonieri, Marco (Seminars in Respiratory and Critical Care Medicine, 2025)
Despite a fairly large number of comparative trials (which are, however, very heterogeneous), the role of corticosteroids in the adjuvant treatment of community-acquired pneumonia remains controversial. Nevertheless, recent randomized trials with adequate power in intensive care unit patients, albeit with conflicting results, have contributed to clarifying our understanding of this issue. More accurate phenotyping of patients likely to benefit from corticosteroid treatment must now be performed. In COVID-19 pneumonia, their benefit is not in question. For certain specific pathogens, including viral pathogens, their indications must be refined. They are still not recommended for influenza. They appear generally safe for short-term use in select populations.
Keywords: corticosteroids; glucocorticoids; community-acquired pneumonia; COVID-19